(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article examines the emergence of the first Islamic state in the Arabian Peninsula, the period of the Rashidun caliphate and the formation of the ruling system of the Arab Caliphate on the basis of primary sources and scientific literature.